Encapsulation of Staphylococcus aureus isolates from mastitic milk: relationship between capsular polysaccharide types 5 and 8 and colony morphology in serum-soft agar, clumping factor, teichoic acid, and protein A. - Sutra, L (1990)
A total of 193 Staphylococcus aureus isolates from bovine, caprine, and ovine mastitis producing type 5 or 8 capsular polysaccharides were investigated for colony morphology in serum-soft agar and agglutinability by an anti-teichoic acid serum, after cultivation in modified staphylococcus medium no. 110. Also, 40 of these strains were cultivated in brain heart infusion and submitted to clumping factor and protein A detection tests. Considering capsular serotyping as a reference method, diffuse growth in serum-soft agar and inagglutinability by anti-teichoic acid serum identified, respectively, 57.5 and 45% of encapsulated strains cultivated in brain heart infusion and 85.5 and 77.2% of those cultivated in modified staphylococcus medium 110. Consequently, these indirect techniques underestimated encapsulation and were greatly influenced by culture conditions. Whatever the medium used, diffuse colony morphology in serum-soft agar was generally characterized by a masking of teichoic acid and protein A. By contrast, these surface antigens were detected in association with compact morphology; the presence of a thin or discontinuous capsular material could explain this result. Moreover, the masking of teichoic acid and the removal of capsular polysaccharide by washing in saline suggest that type 8 capsular polysaccharide is more abundant and labile than type 5.